Gendered Power in Green Economy Practices in Aceh, Indonesia - Hajad, Vellayati; Ikhsan, Ikhsan; Herizal, Herizal (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Climate change and environmental degradation have led Indonesia to implement green economy policies to harmonise economic growth with ecological sustainability and social justice. However, gender mainstreaming remains peripheral within these policy frameworks, especially in regions like Aceh, where Islamic-patriarchal values strongly influence governance and public participation. This study explores how cultural values shape gender dimensions in green economy initiatives in Aceh Province. Using Mary Douglas’ Cultural Theory, extended by Michael Thompson and Steve Rayner, the research analyses how distinct cultural orientations—hierarchical, individualist, egalitarian, and fatalist—affect gender inclusion in environmental policy-making. A qualitative case study approach was employed, drawing on purposive interviews with women activists, government officials, civil society leaders, academics, customary figures, and women involved in agriculture and green entrepreneurship. Thematic analysis, supported by NVivo 12 Plus, was used to uncover dominant cultural narratives, structural barriers, and forms of resistance in gender and environmental governance. Findings indicate that hierarchical cultural norms, reinforced by religious and customary structures, limit women’s roles to supportive rather than strategic functions in policy processes. Nonetheless, egalitarian ideas and transnational feminist movements create space for women’s agency through environmental activism and entrepreneurship. The study underscores the need for gender-responsive and culturally rooted strategies to support a just green transition in Indonesia